Let f(x)=x^2-13 and g(x)=9-x

Perform the composition or operation idicated.

(fg)(-4)=

Please explain how this works

Thank you for the opportunity to help you with your question!

There are two ways to do this:

First you can take f(-4) * g(-4) = [(-4)^2 -13] * [9-(-4)] = [16-13] * [13] = 3 * 13 = 39

Second, you can multiply the two functions: (x^2 -13) (9-x) = 9x^2 - 117 - x^3 + 13x

= -x^3 + 9x^2 + 13x - 117

Then, we plug (-4) in for "x": [-(-4)^3 + 9(-4)^2 + 13(-4) - 117] = 64 + 144 - 52 - 117 = 39

Thank you so much, I just get so confused with how to do it.

Did you understand my explanation?

yes, thank you

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up